2016
DOI: 10.5664/jcsm.5886
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Variability in Apnea-Hypopnea Index during Extended Home Portable Monitoring

Abstract: Study Objectives: Apnea-hypopnea index (AHI) is the primary measure used to confirm a diagnosis of obstructive sleep apnea (OSA). However, there may be significant night-to-night variability (NNV) in AHI, limiting the value of AHI in clinical decision-making related to OSA management. We examined shortterm NNV in AHI and its predictors during home portable monitoring (PM). Methods: Single center prospective observational study of patients (n = 84) with newly diagnosed OSA by polysomnography (PSG) AHI ≥ 5/h. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
6
27
1
Order By: Relevance
“…Our data didn’t show an association between internight variability in AHI and sex, age, sleepiness, or BMI, which agrees with the findings of Prasad et al. 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Our data didn’t show an association between internight variability in AHI and sex, age, sleepiness, or BMI, which agrees with the findings of Prasad et al. 21 .…”
Section: Discussionsupporting
confidence: 91%
“…The quest for a quantified index of respiratory events as a meas- Sixth, how many consecutive nights must be monitored to yield a reliable AHI (Crinion et al, 2020;Le Bon et al, 2000;Prasad et al, 2016;Stoberl et al, 2017)? And, finally, should the procedure be performed in the sleep laboratory or at home ( Apnea A cessation of airflow at the nose and mouth lasting at least 10 s.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…The APAP titration is also monitored for improvement of the patient's OSA with an APAP machine for a longer period than with in-lab titration. Therefore, it is advantageous as reflecting changes in daily sleep and OSA status and is a more comfortable titration method for patients [27]. One study has reported that one week of APAP titration seems sufficient to find an effective and stable PAP level [4].…”
Section: Discussionmentioning
confidence: 99%